1990
DOI: 10.1017/s0952523800005733
|View full text |Cite
|
Sign up to set email alerts
|

A light- and electron-microscopic investigation of the optic tectum of the frog, Rana pipiens, II: The neurons that give rise to the crossed tecto-bulbar pathway

Abstract: The superficial layers of the frog's optic tectum, Potter's (1969) layers A-G, comprise a complex neuropil made up of many afferent axons, the somata of a few neurons, and many dendrites from the neurons located in the deeper layers. Different types of retinal axons are believed to terminate in different layers (Maturana et al., 1960; Kuljis & Karten, 1988; Sargent et al., 1989), but little is known about the relationships between each type of input and the dendrites of the deep tectal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…This type was not found in the present study. These findings in Discoglossus and Eleutherodactylus are consistent with studies in ranid frogs (Rana esculenta, R. ridibunda, R. catesbeiana, R. pipiens) when using HRP or cobaltic lysine as a retrograde and anterograde tracer (Lázá r et al, 1983;Lázár, 1984Lázár, , 1989Tóth et al, 1985;Antal et al, 1986;Hughes, 1990b). In these frog studies, ganglionic cells, pyramidal cells, and large pear-shaped cells were identified as descending projection neurons.…”
Section: Comparison With Anuranssupporting
confidence: 81%
“…This type was not found in the present study. These findings in Discoglossus and Eleutherodactylus are consistent with studies in ranid frogs (Rana esculenta, R. ridibunda, R. catesbeiana, R. pipiens) when using HRP or cobaltic lysine as a retrograde and anterograde tracer (Lázá r et al, 1983;Lázár, 1984Lázár, , 1989Tóth et al, 1985;Antal et al, 1986;Hughes, 1990b). In these frog studies, ganglionic cells, pyramidal cells, and large pear-shaped cells were identified as descending projection neurons.…”
Section: Comparison With Anuranssupporting
confidence: 81%
“…There are a number of different retinal ganglion cell classes in the frog and their terminals end in different tectal layers. Not all classes of retinal ganglion cells project to every tectal cell although it is thought that all layer 6 cells do receive some direct retinal input (Hughes, 1990;Nakagawa et al, 1994). Therefore, if all retinal ganglion cell terminals had nicotinic receptors on them, we would have expected to have seen a nicotine-evoked increase in sPSCs in every tectal cell from which we recorded.…”
Section: Nicotinic Receptor Location In the Optic Tectummentioning
confidence: 97%
“…In anurans the optic tectum provides the main interface between afferent retinal messages and efferent motor commands [1][2][3][4][5][6] . It not only receives retinal signals via direct projections through the optic nerve but also receives them indirectly through various visual pathways, for example, posterior thalamus nucleus, nucleus lentiformis mesencephali (NLM), posterodorsal and posteroventral tegmental nuclei, dorsal horn of the cervical spinal cord, nucleus isthmi and contralateral tectum [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%